Pengembangan laman pembelajaran menulis simpulan berita kelas VIII SMP dengan strategi text based introduction - Islamuddin, Muhammad Nur; Widyartono, Didin (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
Technology-based learning media is favored by students. This research aims to produce a news summary writing page for grade VIII junior high school students with a text-based introduction strategy. The method used is Borg & Gall's research and development modified by the researcher. This study obtained an average score of 85% from validators, an average score of 88% from teachers, and an average score of 85% from students. The material on the page is organized based on the text-based introduction strategy, including the definition of writing the conclusion of the news, the stages of writing the conclusion of the news, and examples of news conclusions. Features in the learning page, namely the material menu, can be added images and videos, the discussion menu as a place to express ideas or ideas, and the assessment menu is used to collect the results of individual student assignments. The learning page is accessed offline using a local network connecting servers and devices.